Climate change, socioeconomic, environmental, and political drivers of road traffic fatalities in Somalia: a multivariate time series analysis - Ahmed, Ahmed Awale; Ali, Abdikadir Abdi; Yousuf Duale, Abdisalan Sh.; Yousuf, Abdirashid M.; Muse, Abdisalam Hassan (Frontiers in Climate, 2025)
IntroductionRoad traffic fatalities (RTFs) in low-resource settings like Somalia are influenced by a complex interplay of socioeconomic, environmental, and political challenges. This study investigates the impact of climate change (temperature, rainfall), environmental degradation (CO2 emissions), socioeconomic conditions (urban population, foreign aid), and political instability on RTFs in Somalia, aiming to contribute to the limited understanding of these dynamics in fragile states.MethodsA multivariate time series analysis was conducted using data from 1984 to 2021. An Autoregressive Distributed Lag (ARDL) model was employed to examine the short-run and long-run effects of the selected drivers on RTFs. The robustness of the model was confirmed through a series of diagnostic tests.ResultsThe ARDL model revealed significant long-run relationships: increased urbanization, CO2 emissions, and political instability were associated with higher RTFs. Conversely, increased rainfall and foreign aid were associated with lower RTFs in the long run. In the short-run, nuanced effects were observed, with both increased temperature and rainfall exhibiting positive associations with RTFs, suggesting immediate, potentially transitory, impacts.Discussion/ConclusionThese findings challenge simplistic explanations of RTF drivers and highlight the necessity of integrated road safety strategies. Such strategies should address climate change adaptation, environmental protection, socioeconomic development, and the promotion of good governance. This research provides valuable insights for evidence-based policymaking aimed at reducing RTFs and achieving Sustainable Development Goals related to health, infrastructure, and sustainable communities in Somalia and similar contexts.